Mary Magdalene [videorecording (DVD)] - Davis, Garth (Director); Mara, Rooney; Phoenix, Joaquin; Ejiofor, Chiwetel, 1977- (Shout! Factory, 2019)
Dramatization of the life of Mary Magdalene, the reformed prostitute who became one of the foremost followers of Jesus Christ during his lifetime.